How focus creates engagement in Primary Design and Technology Education: The effect of welldefined tasks and joint presentations on a class of nine to twelve years old pupils - Looijenga, Annemarie; Klapwijk, Remke M.; Vries, Marc J. de (Design and Technology Education: An International Journal, 2020)
During a Design and Technology class, engagement is both required to start creative hands-on work and a sign of pupil’s creative thinking. To find ways to achieve engagement, we can look to the Montessori tradition. Due to the fact that learning is regarded as feeding insight through experimenting, tasks have to offer pupils the opportunity to gain knowledge about isolated details of the learning situation. This is realised by brief, simple and objective tasks combined with liberty to approach the hands-on work in one’s own way. Applied to Design and Technology, we can define brief, simple and objective tasks with a focus on a technique as an isolated detail of the learning situation. Offering liberty during hands-on work enables creative thinking. The deployment of well-defined tasks with a focus on a technique is possible by dividing a complex assignment into a collection of brief tasks with single problems and working towards single objectives in the topic, making use of a single technique. Such a collection is a format that has the potential to enable ongoing engagement. This case-study researches the actual effect of a stepwise organised collection of tasks on the design performance of pupils of nine to twelve years old. The results show that the tasks turned out to be useful in initiating engagement. In combination with joint presentations, ongoing engagement was achieved resulting in well-considered designs and products. In addition, dialogue with disengaged pupils delivered solutions towards engagement. As a side-effect of dialogue the teacher-pupil relationships and the pupil-pupil relationships improved.